Reviews (New blackfriars, 1966)
HOW COLOUR PREJUDICED IS BRITAIN ? by Clifford S. Hill DARK GHETTO, by Kenneth B. Clark. Victor Gollancz. Ltd. ULTIMATE CONCERN, a Dialogue with Students, by Paul Tillich. Edited by D. Mackenzie Brown THEOLOGY IN RECONSTRUCTION by T. F. Torrance A PRIESTLY PEOPLE by Karl Hermann Schelkle EVERYDAY THINGS by Karl Rahner THE CHURCH AND FREEDOM by Hans Kiing Theological Meditations, edited by Hans Küng. published by Sheed and Ward CREATION & COSMOLOGY, by J. V. Peach. Burns and Oates